2012
DOI: 10.1002/bit.24727
|View full text |Cite
|
Sign up to set email alerts
|

Functional 3‐D cardiac co‐culture model using bioactive chitosan nanofiber scaffolds

Abstract: The in vitro generation of a three-dimensional (3-D) myocardial tissue-like construct employing cells, biomaterials, and biomolecules is a promising strategy in cardiac tissue regeneration, drug testing, and tissue engineering applications. Despite significant progress in this field, current cardiac tissue models are not yet able to stably maintain functional characteristics of cardiomyocytes for long-term culture and therapeutic purposes. The objective of this study was to fabricate bioactive 3-D chitosan nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 52 publications
(52 reference statements)
3
83
1
Order By: Relevance
“…Co-cultures lead to increased extracellular matrix deposition over mono-cultures, including fibronectin deposits in glomerular tissue [19] and collagen deposition and mineralization in bone tissue constructs [20]. Improved function has been demonstrated by co-cultures including beating cardiomyocytes, which increased fluctuations in intracellular calcium ion concentrations not achieved in mono-cultures [21]. Additionally, proper morphology has been observed in co-cultures for cardiomyocytes [21], endothelial cells [18], and epithelial cells [19] not observed when the cells were cultured individually.…”
Section: Strategies For Improving the Physiological Relevance Of Longmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-cultures lead to increased extracellular matrix deposition over mono-cultures, including fibronectin deposits in glomerular tissue [19] and collagen deposition and mineralization in bone tissue constructs [20]. Improved function has been demonstrated by co-cultures including beating cardiomyocytes, which increased fluctuations in intracellular calcium ion concentrations not achieved in mono-cultures [21]. Additionally, proper morphology has been observed in co-cultures for cardiomyocytes [21], endothelial cells [18], and epithelial cells [19] not observed when the cells were cultured individually.…”
Section: Strategies For Improving the Physiological Relevance Of Longmentioning
confidence: 99%
“…Improved function has been demonstrated by co-cultures including beating cardiomyocytes, which increased fluctuations in intracellular calcium ion concentrations not achieved in mono-cultures [21]. Additionally, proper morphology has been observed in co-cultures for cardiomyocytes [21], endothelial cells [18], and epithelial cells [19] not observed when the cells were cultured individually. Improvements in vascular structures can also be achieved with co-cultures over mono-cultures [17, 18, 22].…”
Section: Strategies For Improving the Physiological Relevance Of Longmentioning
confidence: 99%
“…Electrospun chitosan was utilized to provide structural scaffolding characterized by scale and architectural resemblance to the ECM in vivo. Hussain et al studied ventricular CMs from neonatal rats in various culture conditions (i.e., mono-and co-cultures) for their viability and function by using electrospun chitosan-based nanofiber scaffolds [68]. The results demonstrated that the chitosan nanofibers retained their cylindrical morphology in long-term cell cultures and exhibited good cellular attachment and spreading in the presence of the adhesion molecule fibronectin.…”
Section: Natural Polymersmentioning
confidence: 99%
“…The scaffolds are incubated in solutions containing the biological substance, which coats the surface of the fibers. Fibronectin is the most widely used biological substance for cardiac cells and has been coated on chitosan [68], PCL [153] [84], PLA [154] and PU [99]. Collagen type-I was also used on P(L-D,L)LA [111] and laminin on PLGA [121].…”
Section: Co-electrospinning With Conductive Materialsmentioning
confidence: 99%
“…However, pure polymeric nanofibers are suitable mainly for soft tissue engineering, such as reconstruction and regeneration of blood vessels [13,22,23,31,32], myocardium [33,34], heart valves [35,36], skeletal muscle [37,38], skin [15, [39][40][41], tendon and ligament [42,43], intestine [44,45], tissues of the respiratory system, such as trachea and bronchi [46,47], components of urinary tract, such as bladder [48] and urethra [49], visceral organs, such as liver [50,51] or pancreas (pancreatic islets [52,53]), central nervous system, such as brain [6,54,55], spinal cord [56,57], optic system, such as optical nerve [58] and retina [59], and peripheral nervous system [17,60]. Nanofibrous scaffolds can be associated with another advanced technique in recent tissue engineering-controlled delivery of various types of stem cells, such as bone marrow mesenchymal stem cells [51,[61][62][63], adipose tissue-derived stem cells [64,65], neural tissue-derived stem cells [57], and induced pluripotent stem cells …”
Section: Introductionmentioning
confidence: 99%